Preparation of highly effective carbon black supported Pd–Pt bimetallic catalysts for nitrobenzene hydrogenation. (26th July 2021) - Prekob, Ádám; Muránszky, Gábor; Szőri, Milán; Karacs, Gábor; Kristály, Ferenc; Ferenczi, Tibor; Fiser, Béla; Viskolcz, Béla; Vanyorek, László
Abstract: Carbon black (CB) supported palladium–platinum catalysts were prepared with and without nickel(II) oxide or iron(III) oxide promoter materials. By applying ultrasonic cavitation highly efficient CB supported catalysts were created. The designed catalyst preparation is a one-step procedure, as post-treatments (e.g. calcination, hydrogen activation) are not necessary. The activation of the catalysts occurs during their preparation due to the ultrasonic cavitation. Thus, a fast and simple catalyst preparation procedure have been developed. The activity of the catalysts was compared in nitrobenzene hydrogenation at different temperatures in the range of 283–323 K at 20 bar hydrogen pressure. In terms of selectivity and aniline yield, no significant differences were detected even when promoters were present. By using the NiO promoter, the activation energy was extremely low (7.6 ± 0.7 kJ mol −1 ). The selectivity was over 99% in every case, and 99.6% aniline yield was achieved without any promoters (99.7% with NiO), while less than 1.0% by-products were formed. The reaction rate was high with every catalyst, and no significant differences were detected. All in all, the prepared catalysts show excellent catalytic activity in the hydrogenation of nitrobenzene.